Annexins in Influenza Virus Replication and Pathogenesis - Ampomah, Patrick Baah; Kong, Wan Ting; Zharkova, Olga; Chua, Sonja C. J. H.; Perumal Samy, R.; Lim, Lina H. K. (Frontiers in Pharmacology, 2018)
Influenza A viruses (IAV) are important human respiratory pathogens which cause seasonal or periodic endemic infections. IAV can result in severe or fatal clinical complications including pneumonia and respiratory distress syndrome. Treatment of IAV infections are complicated because the virus through antigenic drifts and antigenic shifts, is able to evade host immunity to establish infections making new treatment options desirable. Annexins (ANXs) are a family of calcium and phospholipid binding proteins with immunomodulatory roles in viral infections, lung injury and inflammation. A current understanding of the role of ANXs in modulating IAV infection and host responses will enable the future development of more effective antiviral therapies. This review presents a comprehensive understanding of the advances made in the field of ANXs and IAV research and highlights the importance of ANXs as a suitable target for IAV therapy.